Financial attitude, trust, and ROSCAs' member commitment: Social relations as mediating factor - Siti Amaroh; Husnurrosyidah; Ely Masykuroh (Global Business & Finance Review (GBFR), 2023)
Purpose: This research examines the function of social relationships in the association between financial attitudes and trusts toward member commitment of informal financial institutions, notably the rotating savings and credit association in Indonesia. Design/methodology/approach: The study consisted of 207 female participants, and a partial least square structural equation modelling was utilized to test the hypotheses. All items' validity and reliability were confirmed through inner and outer model testing. Findings: The study found that financial attitudes and trust did not significantly affect commitment but positively influenced social relations. Additionally, social relations impacted commitment and mediated the relationship between financial attitudes, trust, and commitment. Research limitations/implications: Therefore, the study underscores the need to prioritize women and social relationships in informal financial institutions to enhance informal financial inclusion from the grassroots level. Originality/value: These findings highlight the critical role of social cohesion in financial activities and emphasize the potential of informal financial institutions to alleviate short-term liquidity pressures.
Keywords: 650; Social relations; Informal finance; Financial attitude; Trust; Commitment